Sclerostin antibody inhibits skeletal deterioration in mice exposed to partial weight-bearing. (February 2017) - Spatz, J.M.; Ellman, R.; Cloutier, A.M.; Louis, L.; van Vliet, M.; Dwyer, D.; Stolina, M.; Ke, H.Z.; Bouxsein, M.L.
Abstract: Whereas much is known regarding the musculoskeletal responses to full unloading, little is known about the physiological effects and response to pharmacological agents in partial unloading (e.g. Moon and Mars) environments. To address this, we used a previously developed ground-based model of partial weight-bearing (PWB) that allows chronic exposure to reduced weight-bearing in mice to determine the effects of murine sclerostin antibody (SclAbII) on bone microstructure and strength across different levels of mechanical unloading. We hypothesize that treatment with SclAbII would improve bone mass, microarchitecture and strength in all loading conditions, but that there would be a greater skeletal response in the normally loaded mice than in partially unloaded mice suggesting the importance of combined countermeasures for exploration-class long duration spaceflight missions. Eleven-week-old female mice were assigned to one of four loading groups: normal weight-bearing controls (CON) or weight-bearing at 20% (PWB20), 40% (PWB40) or 70% (PWB70) of normal. Mice in each group received either SclAbII (25 mg/kg) or vehicle (VEH) via twice weekly subcutaneous injection for 3 weeks. In partially-unloaded VEH-treated groups, leg BMD decreased −5 to −10% in a load-dependent manner. SclAbII treatment completely inhibited bone deterioration due to PWB, with bone properties in SclAbII-treated groups being equal to or greater than those of CON, VEH-treated mice. SclAbII treatment increased leg BMD from +14 to +18% in the PWB groups and 30 ± 3% in CON ( p  < 0.0001 for all). Trabecular bone volume, assessed by μCT at the distal femur, was lower in all partially unloaded VEH-treated groups vs. CON-VEH ( p  < 0.05), and was 2–3 fold higher in SclAbII-treated groups ( p  < 0.001). Midshaft femoral strength was also significantly higher in SclAbII vs. VEH-groups in all-loading conditions. These results suggest that greater weight bearing leads to greater benefits of SclAbII on bone mass, particularly in the trabecular compartment. Altogether, these results demonstrate the efficacy of sclerostin antibody therapy in preventing astronaut bone loss during terrestrial solar system exploration.